The expressivist objection to nonconsensual neurocorrectives - De Marco, G; Douglas, T (Springer, 2021)
Neurointerventions—interventions that physically or chemically modulate brain states—are sometimes imposed on criminal offenders for the purposes of diminishing the risk that they will recidivate, or, more generally, of facilitating their rehabilitation. One objection to the nonconsensual implementation of such interventions holds that this expresses a disrespectful message, and is thus impermissible. In this paper, we respond to this objection, focusing on the most developed version of it—that presented by Elizabeth Shaw. We consider a variety of messages that might be expressed by nonconsensual neurointerventions. Depending on the message, we argue either that such interventions do not invariably express this message, that expressing this message is not invariably disrespectful, or that the appeal to disrespect is redundant.